Similarities between prion diseases and other neurodegenerative diseases - Hardy, John (Henry Stewart Talks, 2008)
Pathology of diseases, Prion diseases, The first family with a prion mutation: Creutzfeldt-Jacob disease, Alzheimer's disease, 7Mb duplication of locus around APP, APP probably a locus for "sporadic" Alzheimer's disease, Diseases with only Lewy bodies: Parkinson's disease and Lewy body dementia, Iowa kindred structure, alpha-synuclein, Diseases with only Tau pathology, The microtubule associated protein tau, Evolution of human tau haplotypes, Tagging SNPs selection, More complex than just H1/H2, Association with PSP is driven by H1c allele, Primary tauopathies, "Prion-like " behaviour of A-beta, Does the "spreading" of diseases reflect a less extreme version of infection?, Alzheimer's disease is a neuroanatomical disease which "spreads", Parkinson's disease pathology also seems to spread, MAPT and alpha-synuclein in the extracellular compartment?